The Elevated Rate of Cesarean Section and Its Contribution to Non-Communicable Chronic Diseases in Latin America: The Growing Involvement of the Microbiota - Magne, Fabien; Puchi Silva, Alexa; Carvajal, Bielka; Gotteland, Martin (Frontiers in Pediatrics, 2017)
The current recommendation of the World Health Organization (WHO) regarding cesarean section (C-section) is that this clinical practice should be carried out only under specific conditions, when the health or life of the mother/newborn dyad is threatened, and that its use should not exceed 10-15% of the total deliveries. However, over the last few decades, the frequency of C-section delivery in medium- and high-income countries has rapidly increased worldwide. This review describes the evolution of this procedure in Latin-American countries, showing that today more than half of newborns in the region are delivered by C-section. Given that C-section delivery is more expensive than vaginal delivery, its use has increased more rapidly in the private than the public sector; nevertheless, the prevalence of C-section deliveries in the public sector is higher than the WHO’s recommendations, and continues to increase, representing a growing challenge for Latin America. Although the medium- and long-term consequences of C-section delivery, as opposed to vaginal delivery, on the infant health are unclear, epidemiological studies suggest that it is associated with higher risk of developing asthma, food allergy, type-1 diabetes and obesity during infancy. These findings are important, as the incidence of these diseases in the Latin American pediatric population is also increasing, particularly obesity. Though the link between these diseases and delivery mode remains controversial, recent studies indicate that the establishment of the gut microbiota is delayed in infants born by C-section during the postnatal period, i.e. during a critical developmental window for the maturation of the newborn's immune system. This delay may favor the subsequent development of inflammatory and metabolic disorders during infancy. Accordingly, from a public health perspective, it is important to slow down and eventually reverse the pattern of increased C-section use in the affected populations.